ASSOCIAÇÃO ENTRE O POLIMORFISMO ACTN3 R577X E O PADRÃO DE VELOCIDADE DO MOVIMENTO EM PRATICANTES DE MUSCULAÇÃO - ANDRADE, Hennry Barbosa de (2024)
Objective: To evaluate the association between the R577X polymorphism of the ACTN3 gene and the speed of movement execution in bench press and squat exercises among bodybuilding practitioners. The research aims to understand if there is a correlation between this specific genetic variation and muscle performance in bodybuilding practitioners. Materials and Methods: The study was cross-sectional with a quantitative approach. The sample consisted of 22 individuals, including 18 men and 4 women, all over 18 years old. Participants underwent anthropometric evaluation (bioimpedance), saliva collection for genotyping, a one-repetition maximum (1RM) strength test, and movement speed tests in the bench press and back squat with a Smith machine. The study phases were conducted on non-consecutive days: Phase 1: Anthropometric evaluation and buccal mucosa collection. Phase 2: Genotyping. Phase 3: 1RM strength tests. Phase 4: Movement speed tests. A one-way ANOVA test was used to compare the physical strength parameters of participants considering the three genotypes RR, RX, and XX. Results: There were no significant differences in muscle performance among the different genotypes RR, RX, and XX of the ACTN3 gene. Data analysis did not demonstrate a clear association between the R577X polymorphism of the ACTN3 gene and movement speed in bench press and squat exercises. Conclusion: The absence of a significant association between the R577X polymorphism of the ACTN3 gene and muscle performance can be attributed to several factors, such as the complexity of the physical performance phenotype, the influence of other genes and environmental factors, as well as the genetic heterogeneity of the Brazilian population. Despite the limitations, the results contribute to the understanding of the relationship between genetics and physical performance. This study highlights the importance of considering multiple factors when investigating the genetics of muscle performance and suggests that future research with larger samples and more comprehensive evaluations is needed to fully elucidate the role of ACTN3 in physical performance.